Mobilizing Private Finance for Local Infrastructure in Europe and Central Asia : An Alternative Public Private Partnership Framework - Noel, Michel (Washington, DC: World Bank, 2012)
In recent years, the countries of Europe and Central Asia (ECA) have experienced a marked decline in investments by international private operators/investors in local infrastructure-much in line with the trend observed in other emerging markets. This decline has been particularly significant in the local water and energy sectors. In light of the increasingly tight fiscal constraints faced by governments across ECA, there is a strong need to develop alternative Public-Private Partnership frameworks that could attract private investors to the local infrastructure sector. The growing challenge is to identify and implement adequate financing frameworks and modalities of public support Public-Private Partnerships that would be sufficient to attract participation of private investors in local infrastructure without increasing the risk of moral hazard. The objective of this paper is to explore possible elements of an alternative PPP framework that could help governments in ECA to meet this challenge. The paper identifies key impediments to the development of Public-Private Partnerships in local infrastructure in ECA and discusses the elements of the proposed Public-Private Partnership framework.